Multilingual Corpus on Migration and Asylum (COMMIRE) - Anna Beatriz Dimas Furtado; Elisa Duarte Teixeira (Texto Livre: Linguagem e Tecnologia, 2022)
In recent years, the world has faced an unprecedented migration crisis. "Mobilidades e contatos de línguas" (MOBILANG), a research group at the University of Brasilia focusing on the study of language in the context of migration and asylum, has identified that language is the most significant barrier migrants face in accessing essential services after arriving in Brazil. To mitigate this problem, the group envisioned the creation of a multilingual corpus-driven glossary on the subject aimed at translators, interpreters, those who work with migration, and migrants. The glossary is a partnership with the research group "Terminologia e Tradução Direcionadas por Corpus" (TermiTraDiCo), and has the support of the UNESCO Chair on Language Policies for Multilingualism. The initial stage consisted of compiling a robust electronic corpus to serve as the base for the glossary. This paper aims to describe the planning, compilation, and overall content of this corpus, named Corpus Multilíngue sobre Migração e Refúgio (Multilingual Corpus on Migration and Asylum) – COMMIRE, a medium-large corpus containing comparable (and some parallel) texts in Brazilian Portuguese, Spanish, French, and English.